INFLUENCE OF FUNDS FOR RESULTS OF APBD: STUDY IN THE OIL AND GAS INDUSTRY IN INDONESIA - Subawan, Wawan; Padmodiningrat, Sumaryoto (IKRAITH-EKONOMIKA, 2019)
Sharing fund is the proportion possesed by local governments as oil and migas producers. Along with fiscal decentralization and greater local autonomy presently, the sharing fund ought to be used for the wealth of these locals through APBD (Local Planning and Expendfture Budget). This study was aimed at identifying the effect of oil and gas upstream industry sharing fund on APBD. It was an explanative-associative study. Data were collected through interviews, questionairre, observation and Ifterature. Data were analyzed descriptively, and then treated by several assumption tests, approximated through path coefficient and confinnatory factor analysis. Subsequently, the author interpreted and modified the model. The results indicated that the effects of sharing fund on APBD was significant. It means that the greater sharing fund will cause larger amount of APBD.